Romantic Attachment and Difficulties in Emotion Regulation on Dyadic Adjustment: A Comprehensive Literature Review - Fávero, Marisalva; Lemos, Lúcia; Moreira, Diana; Ribeiro, Filipe Nunes; Sousa-Gomes, Valéria (Frontiers in Psychology, 2021)
In romantic relationships, individual differences are determinant factors for relational quality. Specifically, romantic attachment and difficulties in emotional regulation influence each other and may have predictive potential for the perceived dyadic adjustment level. This paper aims to identify the developmental parallel between behavioral patterns built since childhood and the construction of the emotional regulation skills that characterize them. Our analysis was based on the attachment theory and the concepts of romantic relationship and dyadic adjustment. In this way, we sought to further the understanding of relationship dynamics, beyond the usual focus on a single element and on associative relationships, and by exploring other effects among the different dimensions of relational functioning. In particular, we explored the predictive ability of emotional regulation patterns (more flexible individual characteristics) in discriminating between romantic attachment styles (more perennial influences), and their impact on the quality of romantic relationships, in the anticipation of dyadic adjustment variations.